A Blockchain Based Privacy-Preserving Incentive Mechanism for Internet of Vehicles in Satellite-Terrestrial Crowdsensing. (31st January 2022) - Ma, Zhuojia; Wang, Yingqing; Li, Jiawei; Liu, Yang
Abstract : Crowdsensing has been a popular technology recently and has broad application prospects. The Internet of Vehicles (IoV) refers to the effective utilization of static and dynamic information on the network platform through electronic equipment loaded on vehicles and wireless technology, which means there are many devices generating a huge amount of worthy data. However, preserving the privacy of workers and incentivizing them should be concerned. To this end, we apply the satellite-terrestrial system to solve the communication limitation among vehicles. We propose to use blockchain to act as the channel that requesters and vehicles communicate in. Smart contracts are the main designable parts to do the interactions among the participants. Blockchain is tightly related to payment, so that we implement a total payment minimized auction algorithm on it. We carry out extensive simulations and run an experiment on blockchain to find the auction can be implemented as a smart contract and achieve privacy protection.